Lessons from Mount Kilimanjaro : schooling, community, and gender in East Africa - Stambach, Amy, 1966- (Routledge, 2000)
An ethnographic study of a school and community in East Africa focusing on the role school plays in the development of children's identity and relationships to their parents and community, as well as in the development of the region.